2006
DOI: 10.12968/bjon.2006.15.22.22566
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of altered conscious level in clinical practice

Abstract: This article will critically appraise the literature focusing on the use and application of the Glasgow Coma Scale (GCS). Historically the GCS tool was created in a 14-point format and later revised to a 15-point format. Critical analysis of this potentially confusing aspect will be explored. The GCS tool enables the healthcare practitioner to effectively monitor the level of consciousness. The authors believe that anatomical and physiological knowledge is required to competently interpret assessment of level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
25

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 23 publications
0
6
0
25
Order By: Relevance
“…The study showed there is no statistically difference between nurses had a training course about GCS and nurses who hadn't. Previous studies showed that interactive training was successful in improving the knowledge ( Palmer & Knight, 2006;Woodward, 2007;Waterhouse, 2009). We don't have any idea about what training these nurses get and what was the content or method of teaching of this training.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed there is no statistically difference between nurses had a training course about GCS and nurses who hadn't. Previous studies showed that interactive training was successful in improving the knowledge ( Palmer & Knight, 2006;Woodward, 2007;Waterhouse, 2009). We don't have any idea about what training these nurses get and what was the content or method of teaching of this training.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the advent of the GCS, there were no standardized scales used to assess conscious level, and various terms were used, describing the state of consciousness . The GCS provides a common language to report neurologic [ sic ] findings by standardizing descriptions of coma severity and depth and improving communication between health‐care professionals . However, the GCS is not without its weaknesses and limitations .…”
Section: Introductionmentioning
confidence: 99%
“…The GCS is a neurological assessment tool that measures the depth and duration of impaired consciousness and coma in patients with traumatic head injuries and neurological pathologies (Waterhouse 2008). The GCS evolved from the Coma Index (Palmer & Knight 2006), which in turn, was developed based on the Ommaya vital sign card (Cohen 2009). The GCS was developed as a research tool to monitor the conscious level in head injury patients and provide objective assessments of comatose patients (Fischer & Mathieson 2001).…”
Section: Introductionmentioning
confidence: 99%